2018
DOI: 10.1186/s13018-018-0904-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of distal radius fracture in Akershus, Norway, in 2010–2011

Abstract: BackgroundSeveral studies published over the last decade indicate an increased incidence of distal radius fractures (DRF). With Norway having one of the highest reported incidence of DRFs, we conducted a study to assess the epidemiology of DRFs and its treatment in the catchment area of Akershus University Hospital (AHUS).MethodsPatients 16 years or older who presented to AHUS with an acute DRF during the years 2010 and 2011 were prospectively recorded and classified according to the AO fracture classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 32 publications
4
26
1
Order By: Relevance
“…Adjusted for age, sex, and at-risk population, the incidence in 2016 was 24% lower than that in 2001 in the same general population. A recent study from Norway on acute distal radius fractures in one hospital's catchment area (suburban and urban areas in and outside Oslo) during the years 2010 and 2011 showed that the overall annual incidence among inhabitants aged 16 years or older was 19.7 (95% CI 18.7-20.7) per 10,000 [11]. That incidence was lower than the incidence reported in 2 earlier Norwegian studies from Oslo (1-year study period in 1998-1999) [22] and from Bergen (1988) [23], respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjusted for age, sex, and at-risk population, the incidence in 2016 was 24% lower than that in 2001 in the same general population. A recent study from Norway on acute distal radius fractures in one hospital's catchment area (suburban and urban areas in and outside Oslo) during the years 2010 and 2011 showed that the overall annual incidence among inhabitants aged 16 years or older was 19.7 (95% CI 18.7-20.7) per 10,000 [11]. That incidence was lower than the incidence reported in 2 earlier Norwegian studies from Oslo (1-year study period in 1998-1999) [22] and from Bergen (1988) [23], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies conducted in Europe, North America, and Asia, the overall incidence rates of distal radius fracture have been shown to increase over time [6][7][8]. Other more recent studies have shown no change, or even a decrease, in the incidence [9][10][11]. During the last decade, programs for screening and treating osteoporosis have been implemented in health care, potentially affecting the incidence of distal radius fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Distal radius fractures are the most common of all fractures during a lifespan. A Norwegian study found an overall annual incidence of 19.7 per 10,000 inhabitants 16 years or older [ 1 ]. In women, the incidence of distal radius fractures increases progressively with age from the perimenopausal period, while in men, the incidence remains low until later in life [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, when analyzed site by site, the relation with age, which was highly significant in the multivariate analysis for incident MOFs, remained significant only for spine and hip, with a HR for hip of 5.7 for patients older than 70, at any value of BMD. Several epidemiological studies, but not all, have shown that, although hip and vertebral fracture incidence continue to rise steeply with advancing age, that of wrist and other peripheral fractures tend to plateau between 60 and 70. An explanation could be that, because of their better neuromuscular control, younger people are more able to protect themselves with their arms and legs and therefore sustain more distal than proximal fractures …”
Section: Discussionmentioning
confidence: 99%